Excitation of harmonics by flows of the charged particles in the magnetic field - Buts, V.A.; Yegorov, A.M.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2009)
Results of research of the electromagnetic waves excitation by ensemble of relativistic oscillators in a magnetic field are presented. The basic attention is given to studying of generation efficiency of electromagnetic oscillations at harmonics of cyclotron frequency. It is shown, that presence of medium can essentially change efficiency of excitation of high numbers harmonics and all picture of development of oscillators instability. Increments of instability are received. Influence of thermal spread of oscillators is investigated.